UTILIZATION OF THE HEC-RAS METHOD IN ANALYZING INUNDATION AT SUNTER JAYA - Mohammad Immamuddin; Rosyid Al Fiansyah (International Journal of Civil Engineering and Infrastructure, 2023)
Sunter Jaya channel is one of the channels located in Tanjung Priok District, North Jakarta City which is geographically located at 6 Â° 09'31 "South Latitude and 106 Â° 52'08" East Longitude. Sunter Jaya area often occurs inundation when the rainy season arrives when Lake Sunter and Lake Agung excess water capacity. Sediment/sediment factors and lack of awareness of the local community to dispose of garbage in their place. In addition, the growth of some wild plants in the waterways also has the potential to cause disruption to the drainage channel. By conducting an analysis using the Pearson III log distribution method and normal logs and the highest plan of rainfall is taken in the 5 -year period using 28 -year rainfall data obtained from the Kemayoran Rainfall Station which is then calculated by the Thiessen method, it can be found that there are 4 Rainfall Intensity that occurs in the 5 -year period is 192.16 mm in the normal log distribution method, then the mononobe equation is used to find rainfall intensity per hour. , 3,7,8 cannot accommodate rainwater discharge. Therefore, there is a need for additional dimensions to channels 2 from 0.75m x 0.24m to 0.75m x 1m, channel 3 from 0.57m x 0.15m to 0.57m x 0.70m, channel 7 from 0.60m x 0.25m to 0.60m x 1.2m, and channel 8 from 0.50m x 0.28m to 0.50 x 1.2m. With the addition of these dimensions, the channel will be able to work optimally.